A qualitative study of how structural vulnerability shaped COVID-19 testing behaviors in Portland, Maine - Kohut, Michael R.; Sclar, Gloria D.; Nicoll, Leslie; Fernandes, Caroline; Volkers, Andrew; Tucker, Ann; Jacobs, Elizabeth A.; Fairfield, Kathleen M. (Frontiers in Public Health, 2024)
Background: People with structural vulnerabilities (including immigrants, people who use drugs, and those who are unhoused or uninsured) are more likely to experience COVID-19 testing disparities relative to other groups. We documented barriers and facilitators to COVID-19 testing and explored how structural vulnerabilities created and/or exacerbated COVID-19 testing barriers.Methods: Between 2021 and 2022, we conducted semi-structured interviews with 34 members of structurally vulnerable populations and 27 key informants who provide health and social services to them. Our abductive analysis was iterative, utilizing both inductive and deductive coding processes. Recognizing that adequate and appropriate testing for COVID-19 is a complex health behavior that involves both decision-making and issues related to access, we developed of a hybrid model of COVID-19 testing behavior to organize reported barriers. We then used that model for more in-depth analysis of structural vulnerabilities in the context of testing.Results: Our model of testing behaviors provides a framework for understanding the many barriers and facilitators relevant to COVID-19 testing. After identifying locally-reported barriers, we found that specific conditions-economic precarity, legal precarity, the confusing U.S. healthcare landscape, English-exclusive environments, and stigmatizing medical encounters-make adequate and appropriate testing less likely by making COVID-19 testing feel riskier (entailing legal, financial, and psycho-social risks) and making healthcare, and thus vicariously testing, more difficult to access.The COVID-19 pandemic exposed disparities in health care delivery. To avoid undertesting and its associated health consequences during the next pandemic, public health efforts should address structural conditions to ameliorate risks and bolster testing infrastructure to improve access.